Economic Basis of Production of State (municipal) Services in Russia ("Journal "U". Economy. Management. Finance.", 2020)
The article discusses the sources of financial support for the production of state (municipal) services, which are a kind of public good, substantiates the directions for improving the mechanism for their provision to individuals and legal entities at the present stage.
Keywords: public service; region; mechanism; public good; optimization; state